Device-aided therapies (DATs) in Parkinson's disease (PD). The DATs-PD GETM Spanish Registry Protocol Study. - Diego Santos-García; Guillermo González-Ortega; Pilar Sánchez-Alonso; Anna Planas-Ballvé; Rocío García-Ramos; Iria Cabo; Marta Blázquez-Estrada; Álvaro Sánchez-Ferro; DATs-P. D. GETM Spanish Registry Group (PLoS ONE, 2025)
Background and objective Device-aided therapies (DATs) are treatments indicated for people with Parkinson´s disease (PwP) experiencing clinical fluctuations that remain suboptimal despite conventional medication. New DATs have recently emerged such as levodopa-entacapone-carbidopa intestinal gel infusion (LECIG) and subcutaneous infusion of foslevodopa/foscarbidopa (fLD/fCD). Understanding the differences between various DATs is essential. Patients and methods We present here the protocol study of the DATs-PD GETM Spanish Registry. This is a descriptive, observational, prospective, multicenter, open study that is proposed as a clinical registry with progressive inclusion of PwP treated with a DAT in daily clinical practice conditions in more 40 centers from Spain for 10 years. The principal aim is to know the type of DAT that PwP in our country (Spain) receive. Specific objectives are to compare the clinical characteristics of the patients, the effectiveness, safety and tolerability, to identify predictors of a good response and to analyze the response by groups (gender, disease duration, phenotype, etc.). There is a baseline visit (V1; indication of the therapy), start visit (V2; initiation of the therapy) and follow-up visits at 6 months ±  3 months (V3_6M) and after this annually ±  3 months for 10 years (V3_12M, V3_24M, etc.). Results The registry is on going. The first patient was included on April 10, 2024. Patient recruitment and follow-up will be conducted until 31/DEC/2033. It is estimated that the registry will include a minimum of 3,000 patients. Conclusion The present study will help improve the care of PD patients treated with a DAT.